Case report: Systemic multi-organ involvement in an adult-onset immunodeficiency patient infected with Talaromyces marneffei - Li, Kun; Zhang, Yuping; Zhang, Dan; Chen, Qing; Fang, Xueling (Frontiers in Immunology, 2024)
Adult-onset immunodeficiency (AOID) mediated by anti-interferon-γ autoantibodies (AIGA) is a rare condition, particularly prevalent in Southeast Asia and southern China. We present a case study of a 62-year-old female with AOID who developed a severe pulmonary infection caused by Talaromyces marneffei (TM), leading to acute respiratory failure, generalized rash, multiple lymphadenopathies, bone destruction, and a mediastinal mass.Treatment included mechanical ventilation, antifungal medication, and corticosteroids, resulting in complete recovery and discharge. This case underscores the challenges of managing complex infections in AOID patients and highlights the importance of early diagnosis through metagenomic next-generation sequencing (mNGS) and appropriate intervention to improve clinical outcomes.